World Development Report 1996 From Plan to Market. (Washington, D.C. The World Bank, 1996)
This World Development Report examines the transition of countries with alternative systems of centrally planned economies back to a market orientation. These countries seceded from the world market economy between 1917 and 1950 and now face a massive restructuring task. This transition goes beyond typical reforms because the change is deep and systemic, requiring the establishment of key market institutions. This report analyzes two sets of overarching questions. The first series focuses on the initial challenges of transition and how different countries have responded. It examines: (i) whether differences in transition policies and outcomes reflect different reform strategies, or whether they reflect primarily country-specific factors such as economic structure, the level of development, or the impact of simultaneous political changes; (ii) whether strong liberalization and stabilization policies are needed up front, or if other reforms can progress equally well without them; (iii) whether privatization is necessary early in the reform process or at all; and (iv) whether there has to be a gulf between winners and losers from transition. The second set of questions looks beyond these challenges to the longer-term agenda of consolidating the reforms by developing the institutions and policies that will help the new market system to flourish. It focuses on: (i) how countries in transition should develop and strengthen the rule of law and control corruption and organized crime; (ii) how they can build effective financial systems; (iii) how governments should restructure themselves to meet the needs of a market system; (iv) how countries can preserve and adapt their human skills base; (v) why international integration is so vital for transition, and what the implications are for trading partners and capital flows; and (vi) how external assistance can best support countries in transition.
Keywords: Adaptation (Biology); Ecology; Euthenics; Nature and nurture; Banks and Banking Reform; Debt Markets; Economic Theory and Research; Emerging Markets; Environment; Environmental Economics and Policies; Finance and Financial Sector Development; Macroeconomics and Economic Growth; Private Sector Development